2020
DOI: 10.1016/bs.pmbts.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The putative etiology and prevention of autism

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 94 publications
0
21
0
1
Order By: Relevance
“…IGF-1 controls the glucose metabolism in the developing brain. It has significant effects on fetal and perinatal brain growth—especially in neurogenesis, synaptogenesis, and myelination—and participates in several physiologically relevant neuroprotective mechanisms [ 77 ]. Oligodendrocytes, cerebellar Purkinje cells, and motor neurons seem to be particularly sensitive to IGF-1 deficiency [ 78 ].…”
Section: The Biological Basis Of Autism Spectrum Disordersmentioning
confidence: 99%
“…IGF-1 controls the glucose metabolism in the developing brain. It has significant effects on fetal and perinatal brain growth—especially in neurogenesis, synaptogenesis, and myelination—and participates in several physiologically relevant neuroprotective mechanisms [ 77 ]. Oligodendrocytes, cerebellar Purkinje cells, and motor neurons seem to be particularly sensitive to IGF-1 deficiency [ 78 ].…”
Section: The Biological Basis Of Autism Spectrum Disordersmentioning
confidence: 99%
“…The role of vitamin D in brain development and its functions has been demonstrated in multiple animal and human studies, but its specific role in ASD is still unclear, given the multiple confounding factors in the assessment of their relationship [ 59 ]. However, a small open-label prospective study in siblings of probands with ASD found that vitamin D supplementation during pregnancy and breastfeeding or for the first three years of life for those infants that did not breastfeed led to a four-fold reduction in the recurrence rate [ 60 ], possibly through the enhancement of insulin-like growth factor 1 (IGF-1) levels (see below) [ 61 ]. Vitamin D alone or with omega-3 supplementation has been also tried as a secondary measure of prevention in children with ASD, with equivocal results [ 59 , 62 ].…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Lately ASD has been hypothesised to be an insulin-like growth factor 1 (IGF-1)-related brain dysconnectivity; thus, measures to increase the availability of this molecule postnatally could represent a plausible prevention [ 61 ]. This can be attained through breastfeeding for up to one year, and research data has shown that children with ASD were significantly less likely to have been breastfed [ 63 ].…”
Section: Prevention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is relevant to ASD since autistic children below four years old show lower concentrations of IGF-1 than age-matched controls (Riikonen et al, 2006 ). IGF-1 participates in several physiologically relevant neuroprotective mechanisms and exerts significant effects on foetal and perinatal brain growth, including neurogenesis and synaptogenesis (Steinman, 2020b ). The hyperactivation of systemic immune response and specifically the increase in circulating IL-6 in a mother infected by SARS-CoV-2 could expose the foetus to an aberrant inflammatory environment, which is deleterious for the developing brain.…”
Section: Introductionmentioning
confidence: 99%